Quantification of waste heat potential in China: A top-down Societal Waste Heat Accounting Model. (15th December 2022) - Lin, Yuancheng; Chong, Chin Hao; Ma, Linwei; Li, Zheng; Ni, Weidou
Abstract: The recovery of waste heat is important for energy saving and carbon reduction in China. Although numerous technologies for waste heat recovery in China have been analyzed, research is still insufficient to provide an overview of the waste heat potential within the entire energy system. To fill this gap, this paper applies a top-down energy efficiency analysis to develop a Societal Waste Heat Accounting Model to quantify the waste heat potential in China. By indicating the total amount, sector and temperature distribution, and the ability to perform work of waste heat for China in 2018, the results revealed that: a) waste heat occupies 42% of total primary energy inputs, and 26% of primary energy and carbon emissions can be theoretically saved by utilizing waste heat. b) the electricity generation sector is the main source of waste heat, accounting for 45% of the total, of which 88% is below 100 °C. c) the industry sector has a wide range of temperatures, mostly above 300 °C, highlighting the highest ability to perform work. Future studies can focus on the utilization of low-temperature waste heat, which is 66% of the total, for example, the Organic Ranking Cycle technology and the heat pump technology. Highlights: A Societal Waste Heat Accounting model quantified waste heat potential in China. Waste heat potential occupies 42% of total primary energy input in 2018. Most potential exists in the electricity generation and industry sectors. Theoretically 26% of energy savings and carbon reductions by waste heat utilization. The policy priority for the future is the utilization of waste heat below 100 °C.